Materials behaviour analysis of 3D printed brass-PLA filament - Rajan, Dinesh Hasan; Samykano, Mahendran; Suraparaju, Subbarama Kousik; Moorthy, Kohbalan; Kadirgama, Kumaran; Devarajan, Ramasamy; Pandey, Adarsh Kumar (Institute of Physics, 2024)
The current study aims to bridge a crucial gap in existing research, potentially paving the way for a groundbreaking transformation in the development and application of PLA/Brass composites within diverse industries such as aerospace, automotive, consumer goods, and medical devices. The primary objective of this research is to assess the mechanical properties of a composite material made up of Polylactic Acid (PLA) and Brass, produced using Fused Deposition Modelling (FDM) 3D printing technology. Brass, renowned for its exceptional mechanical properties, has been integrated into PLA to form this composite material. The study employs various analytical techniques, including Fourier Transform Infrared Spectroscopy (FTIR), Scanning Electron Microscopy (SEM), and Energy-Dispersive X-ray Spectroscopy (EDX), to scrutinize the chemical and physical characteristics of the PLA/Brass composite. This research revolves around exploring the impact of different printing parameters on the mechanical behavior of the printed specimens. The investigation delves into aspects such as tensile strength, compression resistance, bending properties, and impact resistance. To achieve this, test specimens with varying compositions have been produced using a Raise3D N2 Plus FDM 3D printer, with careful manipulation of printing parameters such as layer height and printing speed. The compositional variations range from 15% wt. to 80% wt., with layer height values spanning 0.25 mm, 0.30 mm, and 0.35 mm, and printing speeds ranging from 20 mm/s to 40 mm/s. The outcomes of this research have revealed the distinct influences of specific printing parameters on various mechanical properties. For example, in the context of tensile testing, it was observed that the combination of a layer height of 0.25 mm and a printing speed of 30 mm/s resulted in the highest elastic modulus. Similarly, the study provides crucial insights into optimizing PLA/Brass composite material properties through controlled additive manufacturing parameters, catering to diverse application requirements. Key findings include an elastic modulus of 0.870 GPa, ultimate tensile strength of 17.53 MPa, yield strength (0.2% offset) of 15.47 MPa, bending strength of 42.25 MPa, bending modulus of 3.679 GPa, compression strength of 33.46 MPa, compression modulus of 5.748 GPa, and energy absorption of 0.246 J. This study advances our knowledge of PLA/brass composite while also providing a chance to create innovative materials.